2015
DOI: 10.2166/wst.2015.450
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dyes from aqueous solutions using activated carbon prepared from rice husk residue

Abstract: The treatment of dye wastewater by activated carbon (AC) prepared from rice husk residue wastes was studied. Batch adsorption studies were conducted to investigate the effects of contact time, initial concentration (50-450 mg/L), pH (3-11) and temperature (30-70 °C) on the removal of methylene blue (MB), neutral red, and methyl orange. Kinetic investigation revealed that the adsorption of dyes followed pseudo-second-order kinetics. The results suggested that AC was effective to remove dyes, especially MB, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The adsorption effect of algae residue biochar on methyl orange molecules becomes worse, thus reducing the removal rate (Subbaiah & Kim 2016;Yu et al 2018). The experimental results are consistent with the conclusions of removing methyl orange dye in an aqueous solution by activated carbon prepared by (Li et al 2016) using rice husk residue and biochar prepared by (Yu et al 2018) using chicken manure. Therefore, to improve the adsorption capacity of algal residue biochar on methyl orange dye solution, the initial pH of the reaction system was adjusted to 2.0 in the other batches of experiments.…”
Section: Effect Of Initial Phsupporting
confidence: 84%
See 1 more Smart Citation
“…The adsorption effect of algae residue biochar on methyl orange molecules becomes worse, thus reducing the removal rate (Subbaiah & Kim 2016;Yu et al 2018). The experimental results are consistent with the conclusions of removing methyl orange dye in an aqueous solution by activated carbon prepared by (Li et al 2016) using rice husk residue and biochar prepared by (Yu et al 2018) using chicken manure. Therefore, to improve the adsorption capacity of algal residue biochar on methyl orange dye solution, the initial pH of the reaction system was adjusted to 2.0 in the other batches of experiments.…”
Section: Effect Of Initial Phsupporting
confidence: 84%
“…The above results showed that when the concentration of methyl orange in the solution was constant, the adsorption sites on the biochar surface also increased accordingly with the increase of biochar dosage. A large number of active sites competed for limited methyl orange molecules, which reduced the amount of methyl orange adsorbed by unit mass biochar (Li et al 2016;Malviya et al 2019;Huang et al 2020), but the removal rate of methyl orange by biochar increased gradually.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%
“…Therefore, although PF is a non-graphitizable material, ACs synthesized from this precursor presents outstanding physicochemical properties, with equal or even better results than most of the graphitizable precursors offering an interesting destination for waste PF [4,24,39,40].…”
Section: Tablementioning
confidence: 99%
“…The main limitation regarding the application of AC in WWTPs is the high cost of the available commercial ACs, for which the used precursors have a great contribution [12]. Therefore, the use of wastes (industrial and agricultural) as new resources to produce ACs is gaining increasing attention since it can be also an alternative management strategy, in line with the new paradigm of a circular and sustainable economy [13,14]. Primary paper mill sludge (PS), a residue derived from the primary treatment of the effluents of the pulp and paper industry, may be a promising precursor of ACs.…”
Section: Introductionmentioning
confidence: 99%